The Analysis of Neurologic Manifestations with Major Electrolyte Abnormalities - Chinthoju, Shirisha; Kancha, Radhika; Murthy, Sindgi Vasudeva; S, MadhuBabu; Smitha, Thungathurthi (Indian Journal of Pharmacy Practice)
Background: Neurologic manifestations caused by the major electrolyte abnormalities in neurologic conditions. The clinical significance of electrolytes in clinical practice and their abnormalities are developing in any of the neurological manifestations and along with other complications. Objectives: The neurological manifestation requires effective management of the electrolyte disorder, which are primarily reversible. In this study we examined electrolyte imbalances that are threatening the life and examined the existent symptoms in neurological patients. Materials and Methods: In this prospective study subjects satisfying the inclusion criteria were enrolled and examined for their neurologic manifestations and analyzed different electrolytes levels. Patients’ demographics, electrolyte investigations, diagnosis and details of neurologic symptoms were noted. Electrolyte levels in various neurologic diseases were compared and correlations between the electrolyte abnormalities and neurologic manifestations made to identify the electrolyte imbalances and preceding symptoms. Results: For this study subjects with symptoms along with pertinent neurological diseases enrolled. A total of 218 patients, of them 161 patients found with electrolyte abnormalities. This study included the patients diagnosed with various neurologic diseases such as spondylosis (66.5%), Migraine (13.7%), Head injury (5.5%), Stroke (5%) and seizures (1.37%) and other conditions (7.79%). The patients’ electrolytes data revealed significant changes in sodium, potassium and calcium electrolyte anomalies resulting in neurologic manifestations. Conclusion: We infer that patients with disturbances in various electrolytes are at high risk for the development of various manifestations. Appropriate recognition, monitoring and management should be done to minimize the effects of the neurological complications.
Keywords: Sodium; Potassium; Calcium; Electrolyte abnormalities; Neurologic manifestations.